The Role of the Creative Process in Holding and Facilitating Traumatic Experience. Issue 3 (2nd July 2016) - Ringel, Shoshana
Abstract: Dissociative self states related to early traumatic experience may be elicited through the creative act, visual images, dreams, enactments, and affective collisions in the analytic dyad. In the following article, the author will describe her work with a visual artist and how the creative process, along with affect sharing and facilitation, helped open pathways to hold and communicate traumatic memories and self states.